PRELIMINARY STUDY OF RED SUPERGIANT RM_1-667 IN THE LARGE MAGELLANIC CLOUD - Gopka, V. F.; Shavrina, A.; Vasilyeva, S.; Yushchenko, A.; Andrievsky, S.; Yushchenko, V. (Одеські астрономічні публікації, 2012)
The observed lines of hydrogen and another strong lines in the spectrum of RM_1-667 (red region of spectra, 5900-7100 Å, spectral type is K7 I) are discussed. Analysis of these lines indicates the presence of mass outflow from the star at a significant velocity. Using the iron lines and the model atmospheres of supergiants (Teff = 3750 K - 4300 K) of the Kurucz’ grid, we obtained the iron abundance lg ε (Fe) = 6.75-7.08, which is equivalent to [Fe/H] equal -0.75 to -0.42.